Postnatal urinary incontinence: prevalence and factors associated with it in a Malaysian population. - MY, Dariah; X, Lily; I, Belan; J, Paterson; Ho, SE; CK Ho, Christopher (Penerbit UKM, 2014)
The aim of this study was to investigate the prevalence of postnatal urinary incontinence (PNUI), the risk factors associated with it and postnatal women’s (PN) level of engagement in practicing traditional Malay confinement care (TMCC) in Kelantan, Malaysia. A cross-sectional survey was conducted among 362 postnatal women aged between 18 – 45 years and who were between three to five months post-delivery. Participants were selected through convenience sampling at six Maternal and Child Health Clinics located in comparatively similar districts. Descriptive and inferential analyses including, factor analysis, Pearson chi-square, Mann-Whitney U test and logistic regressions analysis were used for data analysis. Overall, PNUI was reported by 80 women (22.1%). Vaginal delivery was associated with PNUI. All PN women within the study context practiced TMCC. The findings revealed that women who had PNUI were more likely to engage in a higher level of the ‘Body care’ component of TMCC. UI is prevalent among PN women in Kelantan, Malaysia. Further research into the impact of the ‘body care’ component of TMCC on PNUI is required.